Integrating Interprofessional Collaborative Practice Into Occupational and Environmental Health and Safety Education: Results of a Feasibility Study. Issue 8 (9th August 2022) - McCullagh, Marjorie C.; Valentín-Cortés, Mislael A.; D'Souza, Clive; Batterman, Stuart A.; Neitzel, Richard; Zhen, Harry; O'Neill, Marie S.
Abstract : Introducing interprofessional collaboration competencies into graduate education in worker health and safety is feasible, positively impacting students' knowledge and attitudes regarding other occupational health disciplines. It may also positively impact the ability of occupational health professionals to collaborate in occupational health-oriented multidisciplinary teams and achieve worker health and safety goals. Abstract : Objective: Although occupational health and safety programs are expected to prepare graduates to function in an interprofessional collaborative environment, research to support training in this area is far less common in this discipline than among clinical programs. We incorporated interprofessional education (IPE) competencies into an occupational health and safety course for graduate students in diverse disciplines (public health, engineering, nursing) and evaluated effectiveness. Methods: We assessed course offerings for content learning and attitudes toward IPE and analyzed data using a mixed-methods approach. Results: In general, students increased their understanding of the role of other disciplines, confidence in working in interprofessional teams, and valuation of IPE. Conclusion: Introducing IPE competencies into graduate education in worker health and safety is feasible and can equip students to more effectively work in occupational health–oriented multidisciplinary teams.